Association between physical activity, cardiorespiratory fitness and clustered cardiovascular risk in South African children from disadvantaged communities: results from a cross-sectional study. Issue 1 (14th September 2020) - Müller, Ivan; Walter, Cheryl; Du Randt, Rosa; Aerts, Ann; Adams, Larissa; Degen, Jan; Gall, Stefanie; Joubert, Nandi; Nqweniso, Siphesihle; Des Rosiers, Sarah; Smith, Danielle; Seelig, Harald; et al.
Abstract : Background/Aim: Physical inactivity (PIA) is a growing global health problem and evidence suggests that PIA is a key driver for cardiovascular and chronic diseases. Recent data from South Africa revealed that only about half of the children achieved recommended daily physical activity (PA) levels. Assessing the intensity of PA in children from low socioeconomic communities in low-income and middle-income countries is important to estimate the extent of cardiovascular risk and overall impact on health. Methods: We conducted a cross-sectional survey in eight quintile 3 primary schools in disadvantaged communities in the Port Elizabeth region, South Africa. Children aged 10–15 years were subjected to PA, blood pressure, cholesterol, blood glucose and skinfold thickness assessments. Cardiovascular risk markers were converted into standardised z-scores and summed, to obtain a clustered cardiovascular risk score. Results: Overall, 650 children had complete data records. 40.8% of the children did not meet recommended PA levels (ie, logged <60 min of moderate-to-vigorous physical activity (MVPA) per day). If quartiles were developed based on children's cardiorespiratory fitness (CRF) and MVPA levels, a significant difference was found in clustered cardiovascular risk among children in the highest versus lowest fitness (p<0.001) or MVPA (p<0.001) quartiles. Conclusions: CRF and objectively assessed PA are closely linked with children's clustered cardiovascular risk. Given that 4 out of 10 South African schoolchildren from marginalised communities do not meet international PA recommendations, efforts should be made to ensure that promoting a physically active lifestyle is recognised as an important educational goal in primary schools. Trial registration numbers: ISRCTN68411960 and H14-HEA-HMS-002.